Estudo do controle com Feedforward de potência e realimentação direta aplicado ao retificador Boost Bridgeless com alto fator de potência - Ganacim, Júlio César Secolo (2014)
In this work a study applied in controlled boost rectifiers with high power factor is presented. A most widely used conventional control strategy is the instant average current control, this kind of control have a fast current loop and a slow voltage loop.The cutoff frequency of the voltage loop is low because the output voltage ripple must be twice the frequency of the input network, that need to exist to provide an input current with low harmonic distortion. These controllers feature a high overshoot and a slow transition during the transient load what leads a high voltage in the output capacitors. The developed technique is a digital controller that operate with a feedforward output power associated with one cycle control. This strategy provides better results in the load transient, reducing the overshoot and alloying a reduction of the output capacitor.